EXPERIMENTAL STUDIES OF TRIBOSYSTEMS IN THE PRESENCE OF FULLERENES IN LUBRICANT. PART 1. BY PARAMETER OF TRIBOLOGICAL CHARACTERISTICS OF BASE OIL - Войтов, Віктор Анатолійович; Кравцов, Андрій Григорович (Problems of Friction and Wear, 2021)
The paper presents the results of experimental research aimed at confirming the adequacy of the developed mathematical models method of forming a wear-resistant lubricating film on friction surfaces in the presence of fullerene compositions for different base oils. From the analysis of the presented experimental values and their comparison with theoretical dependences it follows that the mathematical model of formation of a lubricating film on a friction surface of triboelements, which is developed in previous works of the authors, adequately reflects the process of friction and wear and is in a functional relationship with the wear rate and coefficient of friction. Experimental studies have confirmed the theoretically obtained in previous works, the use of fullerene composition, consisting of a solvent-vegetable oil and a fine powder of fullerenes, reduces the rate of wear when changing the tribological properties of base oils by 20,1 ... 22,6%. The simulation error is 6,5 ... 9,2%. Based on experimental studies, it is concluded that the introduction of fullerene composition in base oils with low values of tribological properties reduces the coefficient of friction by 18%. The maximum effect of reducing the coefficient of friction is equal to 71 - 86%, characteristic of base oils with average values of tribological properties. Experimental studies have confirmed that the increase in the concentration of fullerene composition in the base oil from 50 g/kg up to 150 g/kg allows to reduce the volumetric wear rate and the coefficient of friction between these concentrations by 7,8% (theoretical result 6,4%). Therefore, the direction of reducing the volumetric wear rate and friction coefficient by increasing the concentration of the fullerene composition more 100 g/kg can be considered ineffective and experimentally confirmed.